A Dictionary of Egyptian civilization - Posener, Georges (Methuen and CO. LTD, 1962)
"Three thousand five hundred years of Egyptian history are covered in this book. It starts with the prehistoric tribes and ends with the Roman occupation. ... This dictionary is only a dictionary in the sense that the 420 articles are in alphabetical order. Each article is a considered essay in its subject, not a catalogue of facts. Every aspect of Egyptian civilization is covered--politics, art religion, daily life, science and so on. A special feature is the information given about the flora and fauna of Egypt, and their influence on religion and life."